FACILITATING EFFECTIVE CHANGE MANAGEMENT PROCESS IN A DEVELOPMENT BANK IN MYANMAR - Win, Shwe Yee (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2022)
This research investigates to identify the successful intervention of change management in Myanmar’s semi-government bank for systemic organizational change. The research has been done in ‘C’ Bank, Myanmar and employs the 41 respondents including different managerial levels from all departments including General Manager, Manager and staffs. This action research employs structured questionnaires and semi-structured interviews in two phases: pre-ODI and post-ODI. The Pair sample T-test and the contents analysis of the interview passages translated from Myanmar to English for coding are included in data analysis and treatments. The results revel that there is a significant difference between the pre- ODI and the post-ODI of motivating change, creating a vision, developing political support and effective change management. Finding of this study suggest that the analysis on how to sustain the momentum of change in establishing the new organization structure, the impact of organizational structure change on branches, and the employees’ satisfaction with a new structure should study in the future.